2020
DOI: 10.1097/sla.0000000000004310
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Single-use Negative Pressure Dressing in Closed Surgical Wounds After Incisional Hernia Repair

Abstract: Objective: A randomized controlled trial (RCT) was undertaken to evaluate whether the prophylactic application of a specific single-use negative pressure (sNPWT) dressing on closed surgical incisions after incisional hernia (IH) repair decreases the risk of surgical site occurrences (SSOs) and the length of stay. Background: The sNPWT dressings have been associated to several advantages like cost savings and prevention of SSOs like seroma, hematoma, dehiscence, or wound infection (SSI) in closed surgical incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…It was concluded pNPWT should be used in high-risk wounds or obese patients undergoing open VHR, or when anterior compartment separation is used. 85…”
Section: Use Of Drains In Hernia Surgerymentioning
confidence: 99%
“…It was concluded pNPWT should be used in high-risk wounds or obese patients undergoing open VHR, or when anterior compartment separation is used. 85…”
Section: Use Of Drains In Hernia Surgerymentioning
confidence: 99%
“…Eight papers were identified in this review that exclusively addressed prophylactic incisional (closed-wound) negative pressure wound therapy after ventral hernia repair. One had to be discarded because a full text was not found ( 27 33 ). All studies seem consistent in reporting lower rates of SSI and SSO when using pNPWT ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, SSOPI occurred less frequently in the pNPWT group ( p < 0.001). Most recently Bueno-Lledo and colleagues showed a reduction of SSOs from 29.8% to 16.6% ( p = 0.042) comparing 146 patients after ventral hernia repair ( 33 ). This was mainly based on a lower incidence of SSI of 0% in the pNPWT group vs. 8% in the control group ( p = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…Our study findings add to the body of literature on this topic. Several studies have shown promising results with ciNPT for general wound management [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Smolle et al demonstrated a reduction in wound complications in patients who received ciNPT for orthopaedic surgical sites (total joint arthroplasty) and colorectal laparotomy sites [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between diabetes and obesity with poor wound outcomes following DIEP surgeries has been previously well documented [ 5 , 6 , 17 , 18 , 19 ]. Negative pressure dressings have been identified as superior in certain abdominal operations for higher risk patients [ 7 , 8 , 9 , 10 ] and their use is being trialed in more abdominal surgeries such as donor site closure as in our study population. The use of ciNPT showed improved outcomes to a level proportionate to patients without raised risk profiles, although without statistical significance.…”
Section: Discussionmentioning
confidence: 99%